Chain of Legitimacy: Constitution Making in Iceland - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2016)
To understand Iceland's political situation, it is necessary to consider the historical background to the post-crash constitutional revision process launched in 2009. Also, the paper offers a brief account of some aspects of the constitution-making process during 2010-2013, including the work of the Constituent Assembly. Further, the paper describes Parliament's ongoing attempt to undermine the substance of the constitutional bill accepted by two thirds of the voters in the 2012 referendum. A national parliament cannot, without undermining its own legitimacy, allow the results of a constitutional referendum to be changed after the fact, let alone ignored, even if the referendum was advisory.
Keywords: K10; 330; legitimacy; democracy; constitutions; Iceland